Generalised two-component modified weakly dissipative Dullin-Gottwald-Holm system: invariance analysis and conservation laws - Kumar, Sachin; Jyoti, Divya (Mathematical Modelling and Analysis, 2022)
The Dullin-Gottwald-Holm equation models the unidirectional propagation of shallow regime water waves. In this work, the Lie symmetry analysis of the generalised two-component modified weakly dissipative Dullin-Gottwald-Holm system is performed. Using symmetry reduction, the exact solutions are obtained in the form of power series and trigonometric functions. Also using multiplier approach, the conservation laws are obtained. The 3D graphical representations are also shown for obtained solutions.